2019
DOI: 10.1088/1475-7516/2019/08/015
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology and dark energy from joint gravitational wave-GRB observations

Abstract: Gravitational-wave (GW) detectors can contribute to the measurement of cos- Conclusions 39A Catalogs of sources 41

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
202
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(224 citation statements)
references
References 119 publications
(343 reference statements)
20
202
1
1
Order By: Relevance
“…Combining the errors on Ξ 0 from each of the 169 events in Table 5 (taking into account the number of events per bin) we get an overall error ∆Ξ 0 0.7%. This agrees with the result obtained in [203], using the full catalogs corresponding to 10 yr of data, and performing a MCMC to take into account more precisely the degeneracies with H 0 , Ω M and w 0 (and using, conservatively, the current datasets on CMB, BAO and SNe), where it was found that Ξ 0 can be determined to an accuracy of 1%. Clearly, with respect to the size of the deviation of Ξ 0 from the GR value, which can be as large as 80%, this is a remarkable precision.…”
Section: G Detectors: Einstein Telescope and Cosmic Explorersupporting
confidence: 87%
See 3 more Smart Citations
“…Combining the errors on Ξ 0 from each of the 169 events in Table 5 (taking into account the number of events per bin) we get an overall error ∆Ξ 0 0.7%. This agrees with the result obtained in [203], using the full catalogs corresponding to 10 yr of data, and performing a MCMC to take into account more precisely the degeneracies with H 0 , Ω M and w 0 (and using, conservatively, the current datasets on CMB, BAO and SNe), where it was found that Ξ 0 can be determined to an accuracy of 1%. Clearly, with respect to the size of the deviation of Ξ 0 from the GR value, which can be as large as 80%, this is a remarkable precision.…”
Section: G Detectors: Einstein Telescope and Cosmic Explorersupporting
confidence: 87%
“…We next compare the predictions for modified GW propagation of the RT model with the sensitivities of current and future GW detectors, elaborating on the analysis in [115,165,203,204] for ground-based detectors and in [191] Table 6. The events in a given realization of the mock catalog of joint GW-GRB detections for the HLVKI network, over 10 yr of simulated data.…”
Section: Comparison With the Sensitivity Of Current And Future Gw Detmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding detection rates will be impressive, of order 10 5 − 10 6 BH-BH and 7 × 10 4 NS-NS coalescences per year for a single detector such as ET [27][28][29]; depending on the network of electromagnetic facilities operating at the time of 3G detectors, over a few years one might collect O(10 2 − 10 3 ) NS-NS GW events with observed electromagnetic counterpart [29]. The signal-to-noise ratio of many of these events will be huge.…”
mentioning
confidence: 99%